2000
DOI: 10.1021/la0000522
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Sol−Gel Process in the Silica−Metasilicate System. A Microrheological Study

Abstract: The electrochemical quartz crystal microbalance (EQCM) was used to investigate the sol-gel process from an aqueous sodium metasilicate solution at 25°C and pH 3. From the EQCM data it was possible to obtain information on the changing rheological properties of the system during the whole process. Besides sensing changes in the rheological properties, the EQCM detected film formation on the sensor surface. This additional information was used to estimate, using a model for film formation kinetics, the sol parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Case (c): If the solutes cause only thin rigid film formation on the electrode contacting the semi-infinite medium, the resonant frequency will change according to Equation (2) without resistance changes [Eqs. (19) and (20)]: [18] D DR ð Þ ¼ 0 ð19Þ…”
Section: Wwwchemphyschemorgmentioning
confidence: 99%
“…Case (c): If the solutes cause only thin rigid film formation on the electrode contacting the semi-infinite medium, the resonant frequency will change according to Equation (2) without resistance changes [Eqs. (19) and (20)]: [18] D DR ð Þ ¼ 0 ð19Þ…”
Section: Wwwchemphyschemorgmentioning
confidence: 99%
“…Dunn et al introduced alternating current impedance spectroscopy for studies of the evolution of the sol−gel process and gel aging. In addition, Tenan et al applied an electrochemical quartz crystal microbalance to the study of silica gelation from an aqueous silica sol prepared by the hydrolysis of the metasilicate ion . Our study concentrates on characterization of the MTS sol−gel process on platinum substrates by use of gold nanoparticles as markers.…”
Section: Introductionmentioning
confidence: 99%
“…Anglaret et al determined gelation by visually inspecting solution flow properties in a tilted container [7]. Tenan et al used an electrochemical quartz crystal microbalance (EQCM) to monitor the oscillation of a quartz crystal submerged in solution as the solution gels [8]. They showed that EQCM could effectively measure rheological properties using only small-scale perturbations.…”
Section: Introductionmentioning
confidence: 99%